2005
DOI: 10.1111/j.1524-4733.2005.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Adherence of Medications for Chronic Overactive Bladder/Urinary Incontinence in the California Medicaid Program

Abstract: For chronic OAB/UI patients identified in this study, both persistence and adherence with medication treatment were suboptimal. These results suggest that persistence and treatment discontinuation remains problematic for the OAB/UI population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
154
10
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(173 citation statements)
references
References 36 publications
7
154
10
2
Order By: Relevance
“…Discussion Surprisingly, we found much higher persistence rates than previously reported in the literature, with our 1-year persistence rates comparable to the 30-day persistence rates found by others [10,11,14]. The health-care setting with easy access and generous reimbursements might also explain the higher persistence.…”
Section: Resultscontrasting
confidence: 57%
See 4 more Smart Citations
“…Discussion Surprisingly, we found much higher persistence rates than previously reported in the literature, with our 1-year persistence rates comparable to the 30-day persistence rates found by others [10,11,14]. The health-care setting with easy access and generous reimbursements might also explain the higher persistence.…”
Section: Resultscontrasting
confidence: 57%
“…Other studies have shown better continuation rates with once-daily dosing [10,11]. We failed to replicate this finding in the present study, as trospium chloride, prescribed twice daily on an empty stomach, had much better continuation rates than, e.g., tolterodine or solifenacin, which are prescribed without these caveats.…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations